The characteristics of the phenomenon of initiation (sound intonation) in playing the wind instruments - PAWŁOWSKI, Zygmunt; ŻÓŁTOWSKI, Marek (Archives of Acoustics, 1985)
It was found that the phenomenon of initiation in playing the wind instruments was characterized in particular by the value of the rise time of a sound (ET) and the value of the air flow during its duration. The values of the air volume (air output) and prephonation time (TPP) do not characterize significantly the phenomenon described.Analysis was carried out OA the nh7141091 properties related to initiation in playing the wind instruments. The instantaneous values of the air volume and flow rate were measured for the particular phases of playing.30 musicians playing 7 groups of wind instruments were examined. The results of the investigations indicate the usefulness of the method applied in medical and didactic evaluation.